2022
DOI: 10.3390/ijerph19169813
|View full text |Cite
|
Sign up to set email alerts
|

Career Aspiration Fulfillment and COVID-19 Vaccination Intention among Nigerian Youth: An Instrumental Variable Approach

Abstract: COVID-19 is a pandemic of economic significance in the world. Vaccination has been identified as one of the veritable means to address the problem. Few studies have focused on youths’ vaccination intentions and the role of career aspiration fulfillment. This study therefore analyzed the effect engagement with dream jobs has on the willingness to get vaccinated for COVID-19. The data were from the 12th wave of the Nigeria COVID-19 National Longitudinal Phone Survey (NLPS) collected from 974 youths 15–25 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In a cross-sectional study investigating COVID-19 vaccine behavioral intentions among youth in Kenya, the vaccine’s perceived adverse effects were among the critical factors causing vaccine hesitancy [ 40 ]. Finally, a study conducted in Nigeria that compared the attitudes toward vaccines of rural and urban young populations revealed that the young rural population was more willing to vaccinate than the young urban population [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional study investigating COVID-19 vaccine behavioral intentions among youth in Kenya, the vaccine’s perceived adverse effects were among the critical factors causing vaccine hesitancy [ 40 ]. Finally, a study conducted in Nigeria that compared the attitudes toward vaccines of rural and urban young populations revealed that the young rural population was more willing to vaccinate than the young urban population [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is emerging hesitancy toward the COVID-19 vaccine that limits its acceptability and effectiveness in reducing the negative impact of the pandemic on public health. When the COVID-19 vaccine was developed, those who were at high risk of the virus where given priority of vaccination [ 4 ]. The availability of the COVID-19 vaccine may not translate into its uptake; although governments will provide the vaccine, its uptake is voluntary, and people are still hesitant about its effectiveness, side effects, and overall importance [ 5 ].…”
Section: Introductionmentioning
confidence: 99%